2015
DOI: 10.3389/fpls.2015.01151
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Membrane Lipid Order in Root Apex Zones of Arabidopsis thaliana

Abstract: In this study, we used the fluorescence probe, Di-4-ANEPPDHQ, to map the distribution of membrane lipid order in the apical region of Arabidopsis roots. The generalized polarization (GP) value of Di-4-ANEPPDHQ-stained roots indicated the highest lipid order in the root transition zone (RTZ). The cortical cells have higher lipid order than the epidermal cells in same regions, while the developing root hairs show very prominent cell polarity with high lipid order in apical region. Moreover, the endosomes had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
3
13
0
1
Order By: Relevance
“…These lipid order-rich domains are thought to intervene in temporal and spatial organization of cell-specific processes. This differential lipid order was also observed in cell types of Arabidopsis root labeled with di-4-ANEPPDHQ dye [33]. We showed that in Medicago, as in Arabidopsis [33], cortical cells displayed higher lipid order than rhizodermal cells, and that cells from the distal root zones (RAM and RTZ; zones 1 and 2) had higher ordered membranes than the elongated and differentiated cells from the GDZ (zone 4).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These lipid order-rich domains are thought to intervene in temporal and spatial organization of cell-specific processes. This differential lipid order was also observed in cell types of Arabidopsis root labeled with di-4-ANEPPDHQ dye [33]. We showed that in Medicago, as in Arabidopsis [33], cortical cells displayed higher lipid order than rhizodermal cells, and that cells from the distal root zones (RAM and RTZ; zones 1 and 2) had higher ordered membranes than the elongated and differentiated cells from the GDZ (zone 4).…”
Section: Discussionsupporting
confidence: 64%
“…To assess the effect of PEG-induced drought on membrane order, we used the di-4-ANEPPDHQ, a membrane fluorescent probe sensitive to local lipid packing, which has been previously used to monitor membrane lipid order in plant cells [3033]. The spectral properties of the di-4-ANEPPDHQ dye are modified when the membrane environment is changed [34] and a General Polarization (GP) parameter, which defines proportionally the lipid order of the membrane, is calculated from dual-channel images recorded from green and red fluorescence emissions [35].…”
Section: Resultsmentioning
confidence: 99%
“…3, C and D). Considering previous reports that the most highly ordered lipid structures in cells of the transition zone correspond with high auxin flux (Mancuso et al, 2007;Zhao et al, 2015;Baluška et al, 2018), we speculate that phosphorylated NRT1.1 may aggregate into the PM microdomain in a process triggered by LN, which might provide an efficient means for transporting auxin.…”
Section: Discussionmentioning
confidence: 56%
“…Averaging the RGM of cells in specific root zones, we observed increasing values of RGM corresponding to a decreasing distribution of the level of PM order along growing tips of A. thaliana roots ( Figure 1B). Such highest PM order of the apical region was already observed in root epidermal cells 8 and could be related with the cytokinesis-induced formation of ordered domainenriched platforms. 9 These results suggest a correlation between plant cell PM order and cell differentiation.…”
supporting
confidence: 58%